An empirical test of upper-echelon theory - Norburn, David; Birley, Sue (Cranfield School of Management, 1986)
This research tested the validity of Hambrick and Mason's (1985)upper-echelon theory which posits that the characteristics of top executives will explain, partially, finanical performance variations within industries. Data was obtained from 953 top managers, the dominant coalition of the largest 150 companies within five US industries - Dairy, Footwear, Tyres, Mobile Homes and Machine Tools. Results were generally supportive: managerial characteristics not only predicted performance variations within industries - the top performers having significantly different managerial profiles than poorly performing companies - but also that the characteristics of managers within high performing companies were similar across the five industries. This greatly increases confidence in prediciting superior organisations, and enables the management development function to improve the chances of commerical success of future top managers.